Participation of women in STEM higher education programs in Latin america: The issue of inequality (2020)
The low participation of women in STEM fields has been considered a critical issue in our society. It affects the rights of women to receive high quality education, to develop their skills and to improve their career prospects. Additionally, it has a negative impact on the outcomes of science and engineering projects. This paper describes the methodology and preliminary results of the application of an instrument to measure indicators for gender equality in STEM programs. The SAGA survey, developed by UNESCO, was applied in fifteen European and Latin American universities within the framework of the W-STEM project. This paper presents the results of nine Latin American universities related to gender equality in student population and teaching staff, as well as attraction, access, and graduation of female vs male students. The gender gap is evident in all the indicators, so it is necessary to define policies and strategies to face this issue from different levels